2020
DOI: 10.18203/2349-3259.ijct20200538
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid profile in pulmonary tuberculosis patients: a prospective study in a tertiary medical college of southern Odisha

Abstract: Background: Globally, an estimated 10.0 million (range, 9.0 to 11.1 million) people infected with tuberculosis (TB). Developing country like India accounts for one fourth of the global tuberculosis burden. TB is associated with diffuse functional impairment of most endocrine organs. Methods: We conducted a study to evaluate the thyroid profile status in new sputum positive pulmonary tuberculosis patients, aged 12 years and above; attended and admitted to chest and TB, Medicine Department of SLN MCH, Koraput, O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…A study from India indicated a comparable proportion (2.4%) of overt hypothyroidism with our study. 28 However, the same study reported from India showed a lower euthyroid proportion (58.21%) 28 than the current study.…”
Section: Discussioncontrasting
confidence: 46%
“…A study from India indicated a comparable proportion (2.4%) of overt hypothyroidism with our study. 28 However, the same study reported from India showed a lower euthyroid proportion (58.21%) 28 than the current study.…”
Section: Discussioncontrasting
confidence: 46%
“…Dash M et al . [ 30 ] found sick euthyroid syndrome in 35.82% of TB patients. Subclinical hypothyroidism increases the risk of depression and reduces adherence to MDR-TB and HIV treatment.…”
Section: Discussionmentioning
confidence: 99%